2021
DOI: 10.1039/d1ra00227a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of core–shell Ce-modified mixed metal oxides derived from P123-templated layered double hydroxides

Abstract: A shell of P123-templated CeMgAl-LDO was distributed in transverse and longitudinal directions on spheres of SiO2. The composites displayed high catalytic activity in the synthesis of propylene glycol methyl ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, the previous study of our research group 41 found that the aggregation of CeO 2 particles would affect the catalytic performance of the catalyst, and the doping amount of Ce in the LDOs material should not be too large, so we optimized the doping amount of Ce through experiments as well ( Fig. 9a ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the previous study of our research group 41 found that the aggregation of CeO 2 particles would affect the catalytic performance of the catalyst, and the doping amount of Ce in the LDOs material should not be too large, so we optimized the doping amount of Ce through experiments as well ( Fig. 9a ).…”
Section: Resultsmentioning
confidence: 99%
“… 39 However, core–shell materials containing silica as a core and more than two elements in the LDH shell have not been thoroughly examined. To date, only three structures, SiO 2 @CeMgAl-LDH, 49 SiO 2 @MgAlFe-LDH and SiO 2 @MgAlNi-LDH, 50 have been described in detail.…”
Section: Introductionmentioning
confidence: 99%